2007
DOI: 10.2466/pr0.101.5.67-78
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Cooperative Norm in Predicting Organizational Citizenship Behaviors From Procedural Justice Climate

Abstract: Although the relationships between procedural justice climate and organizational citizenship behaviors have been examined in recent years, little research has explored the mechanism by which procedural justice climate shapes individual employee prosocial behaviors in the workplace. The purpose of this study was to examine the mediating role of a group-level cooperative norm on the relationships between the group-level procedural justice climate and individual-level organizational citizenship behaviors. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In addition, social exchange theory posits that fairness communicates the symbolic message of respect (in other words, being treated fairly means one is a respected member of a unit), thus allowing team members to achieve a high level of self-worth and esteem, which in turn may increase their willingness to perform at a higher level to contribute to the successful performance of the team (Tyler & Blader, 2003). Past research has identified cooperative teamwork process as a key mechanism mediating the relationship between organizational characteristics and criterion variables such as performance and team member reactions (Cropanzano, Li, et al, 2011;Lin et al, 2007). In a similar vein, when team members perceive an environment characterized by a high level of fairness, they may engage in more cooperative behaviors, which may in turn improve the performance of the team and foster a satisfactory team experience (LePine, Piccolo, Jackson, Mathieu, & Saul, 2008).…”
Section: Effects Of Peer Justice Climate and Justice Climatementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, social exchange theory posits that fairness communicates the symbolic message of respect (in other words, being treated fairly means one is a respected member of a unit), thus allowing team members to achieve a high level of self-worth and esteem, which in turn may increase their willingness to perform at a higher level to contribute to the successful performance of the team (Tyler & Blader, 2003). Past research has identified cooperative teamwork process as a key mechanism mediating the relationship between organizational characteristics and criterion variables such as performance and team member reactions (Cropanzano, Li, et al, 2011;Lin et al, 2007). In a similar vein, when team members perceive an environment characterized by a high level of fairness, they may engage in more cooperative behaviors, which may in turn improve the performance of the team and foster a satisfactory team experience (LePine, Piccolo, Jackson, Mathieu, & Saul, 2008).…”
Section: Effects Of Peer Justice Climate and Justice Climatementioning
confidence: 97%
“…In the present study, we bring this body of literature to the unit level by evaluating peer justice climate and justice climate as higher-level constructs with three justice dimensions serving as their indicators, respectively. Third, past research has shown that peer justice climate and justice climate influence team outcomes through mechanisms such as teamwork process (Cropanzano, Li, et al, 2011) and team cooperative norms (Lin, Tang, Li, Wu, & Lin, 2007). However, these studies tend to examine one source of justice perceptions at a time.…”
mentioning
confidence: 97%
“…Specifically, distributive justice, procedural justice, and interactive justice have all been found to have weak to moderate positive correlations with individual job performance and OCBOs and OCBIs (see Colquitt et al, 2001). More recent research on justice climates also showed a positive effect on team performance and behavioral outcomes (e.g., Ambrose et al, 2013;Cole et al, 2013;Colquitt et al, 2002;Erdogan & Bauer, 2010;Liao & Rupp, 2005;Lin et al, 2007;Naumann & Bennett, 2002;Rupp & Cropanzano, 2002). Based on the group-value theory of justice and taking into account the contextual factors of Chinese culture and economic development as well as previous findings at the individual and group-levels, we propose that group justice climates enhance group effectiveness by means of fostering group harmony and such mediating effect also accounts for the differential effect of the three types of justice climates on team performance and team helping.…”
Section: Mediating Effects Of Group Harmonymentioning
confidence: 98%
“…The growing literature on justice climates has conceptualized organizational justice as a collective or group-level construct as opposed to the earlier studies that examined justice as an individual-level phenomenon. The justice climate research, however, has focused mostly on procedural justice climate (e.g., Cole, Carter, & Zhang, 2013;Colquitt, Noe, & Jackson, 2002;Lin, Tang, Li, Wu, & Lin, 2007;Naumann & Bennett, 2002), with some attention to interactional justice climate (e.g., Rupp & Cropanzano, 2002), while distributive justice climate being mostly neglected except a few studies (e.g., Ambrose, Schminke, & Mayer, 2013;Erdogan & Bauer, 2010;Whitman, Carpenter, Horner, & Bernerth, 2012). Moreover, more research is needed that explores the relative impact of the distributive, procedural, and interactional justice climates on different types of group-level variables (e.g., process vs. outcome; agentdirected vs. system-directed) (Whitman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation